(untitled) (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2023)
This paper reports on the community service program of the invention of a virtual museum with a strong emphasis on Fuad Muhammad Syafruddin’s murder case. The author organizes this program using the concept of digital humanities by making a virtual museum and digital map of the case, the iconic violence against Indonesian journalists. It needs to manage a collective memory of violence against journalists in Indonesia, including the murder of Yogyakarta BERNAS journalist Fuad Muhammad Syafrudin (Udin), which has entered its 24th year. The public documents related to the case are rich, among other ten books written by journalists and academics and reports from civil society organizations such as those from LBH Indonesia and Kontras. Problems arise when these books and information are located separately in the archives of many institutions, not stored in a single and integrated data channel. Most publications related to Udin are in printed format, such as books and statement sheets, which are prone to lose. The program partnered with the Alliance of Independent Journalists (AJI) Yogyakarta. It was held in October-December 2020 and resulted in a digital museum and interactive map: http://www.indonesiapena.info/. This virtual museum, as well as the virtual map of the historic location of the Udin’s case in Yogyakarta, helps AJI Yogyakarta and the journalist community in Indonesia to maintain their memory of the case and, more importantly, it also allows the general public to trace the histories of Indonesian journalists easily. — Paper ini menjelaskan kegiatan pengabdian masyarakat pembuatan museum virtual tentang kasus kekerasan terhadap jurnalis, khususnya pembunuhan Fuad Muhammad Syafrudin. Program ini dilaksanakan memakai konsep digital humanities, berupa pembuatan museum virtual dan peta digital kasus Udin sebagai salah satu ikon kekerasan terhadap wartawan. Tujuan pengabdian adalah untuk merawat memori kolektif publik atas kasus pembunuhan jurnalis harian BERNAS Yogyakarta Fuad Muhammad Syafrudin (Udin) yang sudah memasuki tahun ke-24. Dokumen publik terkait kasus Udin paling banyak dibanding kasus kekerasan wartawan lain di Indonesia. Tercatat ada 10 buku tulisan jurnalis dan akademisi dalam dan luar negeri, dan berbagai laporan masyarakat sipil seperti dari LBH Indonesia dan Kontras Jakarta. Problemnya, buku dan laporan ini berada terpisah dalam arsip di berbagai lembaga terkait, tidak terkonsolidasi pada satu kanal data. Mayoritas produk publikasi yang terkait kasus Udin berformat cetak seperti buku dan lembaran pernyataan sikap yang rawan hilang. Pengabdian ini berpola partisipatif, karena mitra pogram Aliansi Jurnalis Independen (AJI) Yogyakarta terlibat dalam kegiatan dari awal hingga akhir, bulan Oktober-Desember 2020. Dari program ini, lahir museum dan peta virtual interaktif pada link: http://www.indonesiapena.info/. Museum dan peta lokasi kasus Udin di Yogyakarta berbasis digital ini membantu AJI Yogyakarta dan komunitas jurnalis di Indonesia untuk merawat memori atas kasus kekerasan terhadap mereka dan juga membantu publik untuk menelusuri data sejarah jurnalisme.